PENGARUH SERVICE QUALITY DAN CORPORATE BRAND IMAGE TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA BANK MANDIRI SURABAYA - PURNAMA, HANS (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Reasearch objective is to test and analize influence Service Quality dan Corporate Brand Image in Bank Mandiri Surabaya to Customer Satisfaction and Customer Loyalty. The benafit of this reasearch is to provice suggestion to Bank Mandiri Surabaya to improve their performace and give the best quality for customer. The variable of study is Service Quality, Corporate Brand Image, Customer Satisfaction, Customer Loyalty. The reasearch us Structural Equation Modelling as analysis technique. The finding in this study shows that Corporate Brand Image and Customer Satisfaction doesn’t have any significant affect. The other relationship which is Service Quality and Customer Satisfaction show no significant affect. In this reasearch the variable which show significant relationship is Corporate Brand Image and Service Quality . The other one is Customer Satisfaction and Customer Loyalty.